ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI UNDERPRICING SAHAM - Afifah Lania Sihotang; Yenni Samri Juliati Nasution; Arnida Wahyuni Lubis (Universitas 45 Surabaya, 2023)
In this study, only seven factors will impacting the underpricing of shares in companies conducting an IPO to obtain additional capital on the IDX. Data collection is done through IDX with a sample of 30 companies. Data analysis uses the F Test method, T Test, Multiple Regression Analysis, and Determinant Test. With test F, the value of F k is the seventh free variable of 32.171 and Sig. < α (α = 0.05) is 0.01. That is, H0 is rejected and H1 accepted. There is also significant impact simultaneously from ROA, EPS, DER, Underwriter Reputation, Auditor Reputation, Company Age, and Company Size on Underpricing. In multiple regression analysis, ROA has a coefficient of 0.09. A positive value coefficient that means the direction of ROA regression is positive. In Partial Test (Test T), ROA has a Sig. value 0.93 (>0.05) which means H0 is accepted. ROA does not have a significant impact on underpricing. In regression analysis multiple EPS coefficient of 1.117 and in Test T Sig. value 0.003 (<0.005) which means H1 is accepted. EPS has a significant influence on underpricing. In regression analysis multiple coefficients DER -0.009 and in Test T sig value. 0.295 (< 0.005) which means H0 is accepted. DER has no significant effect on underpricing. On regression analysis the underwriter reputation coefficient -1.814 and on test T Sig. 0.194 (> 0.05) which means H0 is accepted. The reputation of the underwriter does not have significant impact on underpricing. In regression analysis multiple auditor reputation coefficients -2,040 and on the Sig. T Test. 0.372 (> 0.05) which means H0 is accepted. The reputation of the Auditor has no significant influence over underpricing. In regression analysis multiple Company Age coefficient -0.18 and on Test T Sig. 0.719 (>0.05) which means H0 is accepted. The age of the Company does not have significant impact on underpricing. In regression analysis multiple coefficients of Company Size -0.91 and on Test T 0.01 (< 0.05) which means H0 is rejected H1 is accepted. Size of the Company (X7) has a significant influence on underpricing. Then, R2 was obtained by 0.706 and adjusted R value of 0.79. It can be said that 79.1% of dependent variables could be explained by independent factors. while the rest is caused by the others that are not contained in this study.